An online event as a product of the active learning methodology: an experience via pbl at the university of Brasilia-Brazil - Mariano, Ari Melo; Mello , Joao; Monteiro, Simone Borges Simão; Martin, Adriana Regina (Journal of Management and Business Education, 2018)
The objective of this study was to suggest an alternative for managing the knowledge gained and resulting legacy from the application of the Problem Based Learning (PBL) method in a higher education context. The legacies of the PBL method are found to be more profound and diverse than those related to either the students' experience or the projects developed to solve real-world problems presented by external agents (the partners of the UnB Production Engineering course). The Production Engineering course has, since 2011, adopted the PBL method as an active learning methodology. Although each semester presents new opportunities in the process of consolidating this method, it’s been perceived that the many phases and results of this process are often utilized in real time only, contributing to the participating individuals exclusively as they occur. This is seen as a type of temporal result, seen only at a given "T" moment in the discipline’s lifecycle. Correspondingly, part of this knowledge is currently seen as perishable, since it is not possible to store it for future moments. In an attempt to extend this experience, starting in 2016 the University of Brasilia’s Production Engineering course has begun to develop an extension of PBL products by means of distinct events. The results haven been satisfactory, thus far involving 458 students and 7910 participants. As a legacy, it was possible to create a platform for the presentation of active learning methodologies and the exchange of experiences. Thus, the project presentations, once seen as distinct landmarks, became part of a legacy through a specific event, assisted and accessed as a course memory and a student’s digital portfolio.